Analisis Pengaruh Kualitas Informasi, Kualitas Sistem dan Kualitas Layanan terhadap Kepuasan Pengguna Sistem Informasi Akademik (SIAKAD) - Venezia Thalia Metekohy; Noya, Rylano Stefano (Yayasan Literasi Sains Indonesia, 2025)
Sistem Informasi Akademik (SIAKAD) is one of the systems used by students of the Faculty of Economics and Business, Universitas XYZ to help obtain information related to academic information which includes student data, lecturer data, grades, class schedules, as well as reasearch results and scientific publications. The study adopts variables in DeLone & McLean Information System Success model, excluding the variables of use and net benefits to better align to determine the extent to which information quality, system quality, and service quality influence user satisfaction with the academic information system. The sample was determined using purposive sampling with specific criteria, resulting in 181 respondents. Data were collected through the distribution of questionnaires. The analysis technique employed in this study is quantitative descriptive analysis using multiple linear regression. The results indicate that information quality and service quality have a significant influence on user satisfaction, while system quality does not have a significant effect on user satisfaction with the Academic Information System (SIAKAD).